Pengaruh EM4 Terhadap Pengolahan Limbah Cair Industri Tahu Menjadi Pupuk Organik Cair - Nabilah Rizqi Qurrotu’aini; Mintan Mawarni; Yoshua Beay; Nurrochman (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Household waste contains high enough organic pollutants which can be used as raw material for liquid organic fertilizer. The addition of EM4 (Effective Microorganisms) in the manufacture of fertilizers aims to accelerate the process of making organic fertilizers effectively and EM4 can also improve the quality of the fertilizer. The method used in the manufacture of this fertilizer is an anaerobic method. The tofu industry liquid waste is accommodated in tubs that have been labeled A and B. Then the same treatment is given, namely the addition of 750 mL of coconut water for every 3 liters of tofu industrial liquid waste and 90 grams of granulated sugar in each tub. In the tub labeled B, 90 mL of EM4 was added. The tub to which these ingredients have been added is then closed tightly and fermented for 14 days. Parameters tested include pH, temperature and also levels of C-Organic. After 14 days of fermentation, the pH obtained was 4. The pH of the liquid organic fertilizer decreased because the C-Organic decomposed in the fermentation of this liquid organic fertilizer into organic acids. C-Organic content after fermentation for sample A was 0.57% and C- Organic content for sample B was 0.42%. The low levels of C-Organic are due to the addition of EM4 during the fermentation process which can break down compounds such as carbohydrates and proteins into simpler compounds that can later be utilized by plants. This standard of liquid organic fertilizer is adjusted to the Regulation of the Minister of Agriculture no. 70/Permentan/SR.140/10/2011. Liquid organic fertilizer with the addition of EM4 will affect the yield of C-Organic content.